2008
DOI: 10.2527/jas.2007-0595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with selenium-enriched yeast or sodium selenite on selenium tissue distribution and meat quality in beef cattle1

Abstract: The objective was to determine the concentration of total Se and the proportion of total Se comprised as selenomethionine (SeMet) and selenocysteine (SeCys) in postmortem tissues of beef cattle offered diets containing graded additions of selenized enriched yeast (SY; Saccharomyces cerevisiae CNCM I-3060) or sodium selenite (SS). Oxidative stability and tissue glutathione peroxidase (GSH-Px) activity of edible muscle tissue were assessed 10 d postmortem. Thirty-two beef cattle were offered, for a period of 112… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
100
5
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 32 publications
21
100
5
3
Order By: Relevance
“…In addition, there were no appreciable differences between the two Se sources in terms of both GSH-Px activity and whole blood SeCys, whereas SeMet contents were greater in SY-supplemented birds. This observation in turkey poults is unlike those reported for lambs (Juniper et al, 2008a), beef cattle (Juniper et al, 2008b) and dairy cattle (Phipps et al, 2008) that had received similar sources and doses of supplementary Se, in which SeCys was the predominant selenized AA, irrespective of treatment.…”
Section: Selenium Content In Tissuescontrasting
confidence: 94%
See 4 more Smart Citations
“…In addition, there were no appreciable differences between the two Se sources in terms of both GSH-Px activity and whole blood SeCys, whereas SeMet contents were greater in SY-supplemented birds. This observation in turkey poults is unlike those reported for lambs (Juniper et al, 2008a), beef cattle (Juniper et al, 2008b) and dairy cattle (Phipps et al, 2008) that had received similar sources and doses of supplementary Se, in which SeCys was the predominant selenized AA, irrespective of treatment.…”
Section: Selenium Content In Tissuescontrasting
confidence: 94%
“…Glandular visceral tissues tend to have greater total Se concentrations than muscle, and cardiac muscle has a greater total Se content than skeletal muscle. These data agree with those reported in laying hens (Petrovič et al, 2006;Pan et al, 2007) and broilers (Wang and Xu, 2008) and are also similar to those reported in lambs (Juniper et al, 2008a) and beef cattle (Juniper et al, 2008b). The differences seen in cardiac, skeletal and gizzard muscle tissue total Se concentrations, when comparing comparable doses of the two sources of Se, are indicative of improved Se uptake and incorporation within those birds supplemented with SY.…”
Section: Selenium Content In Tissuessupporting
confidence: 90%
See 3 more Smart Citations